PEDAGOGICAL FUNDAMENTALS OF INNOVATIVE MANAGEMENT OF EDUCATIONAL INSTITUTIONS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article explains the best principles of innovative development of educational institutions and their management from the very first principle to the socio-economic principle of the developing country